CRYPTOGRAPHY OF CHACHA20 and RSA ALGORITHMS for TEXT SECURITY - Dzahabi, Ziad Yasqi; Hayaty, Nurul; Bettiza, Martaleli (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
The purpose of this study is to apply the ChaCha20 and RSA cryptographic algorithms to enhance text security and safeguard data from unauthorized access, data breaches, and cyberattacks such as man-in-the-middle or replay attacks. ChaCha20, a symmetric encryption algorithm, is employed for generating efficient and secure keystreams, while RSA, an asymmetric algorithm, is used for encrypting numeric keys or messages. The integration of these two algorithms ensures robust data protection from various digital threats. The choice of this title stems from the growing urgency to prioritize data security in the digital era, especially given the increasing incidents of data leaks that often lead to significant consequences. This research focuses on analyzing the implementation of both algorithms in encryption and decryption processes, as well as evaluating their effectiveness in preserving data confidentiality and integrity. The findings of this study demonstrate that the ChaCha20 and RSA implementations effectively secure data, with the encryption and decryption processes functioning as intended. To further validate the system’s robustness, simulated attacks were conducted, and the results confirmed the system's ability to prevent unauthorized access. This research not only contributes to the development of reliable data security solutions but also highlights opportunities for future improvements. Enhancing algorithm efficiency and optimizing encryption runtime are potential areas for further exploration. By addressing these challenges, the study aims to pave the way for more robust and efficient cryptographic solutions in the evolving landscape of digital security.